Design and Development of A Semi-Automatic Catfish Feeder Device Based on Arduino - Sugandi, Gandi; Gusman, Dilla Oktaviani; Susilawati, Helfy; Wiharso, Tri Arif (Teknik Elektro Universitas Siliwangi, 2025)
Fish feed is one of the most important factors in fish farming and plays a crucial role in determining the success of the cultivation. One of the most commonly farmed fish species in the community is catfish. The feeding of catfish must be carefully managed to optimize their growth by providing feed accurately and regularly so that they can be harvested with maximum results. In this thesis research, a semi-automatic catfish feeder was designed to optimize the feeding process. The device is designed with a semi-automatic system so that when monitoring the catfish pond, farmers can simultaneously feed the fish. This device also uses a solar panel as an energy source to make it more efficient, especially in areas far from electrical sources. The feeder operates using Bluetooth transmission and can be controlled via a smartphone. It includes a feed dispensing system and a feed weight monitoring system, which displays the feed weight in grams on an LCD screen. On the smartphone, a parameter called